Exploring Digital Transformation Readiness: Unveiling Hidden Patterns Through K-Means Clustering - Lalita Vistari; Issy Yuliasri; Yuliati -; Adrallisman -; Melfa Lamria Berliana Lumbantoruan (Universitas Pendidikan Ganesha, 2025)
The rapid digital transformation in higher education requires students to have advanced digital skills, ethical awareness, and effective communication. However, many studies overlook the diversity within student populations, particularly in terms of digital readiness. This research addresses this gap by examining students' digital construction variations through the use of K-Means clustering. The study adopts a mixed-methods approach, combining a survey on technology usage, attitudes, and communication with qualitative interviews. The analysis identifies two distinct student clusters: